An Evaluation of Access Bank Nigeria Plc’s Corporate Social Responsibility Practice in Nasarawa State - Dangana, Owusoweshi Michael; Okujeni, Richard (EDUMALSYS Journal of Research in Education Management, 2025)
Corporate Social Responsibility (CSR) represents the ethical obligation of organizations to contribute positively to society beyond their business operations, addressing social, environmental, and economic well-being while fostering responsible engagement with stakeholders and host communities. This study evaluates the CSR initiatives of Access Bank Nigeria Limited in Nasarawa State, guided by Stakeholder Theory. Adopting a survey research design, questionnaires were administered to 365 respondents across selected Local Government Areas. The study sought to determine whether Access Bank implements CSR activities in the state, identify specific initiatives, assess community awareness, and evaluate the alignment of these initiatives with local needs. Findings revealed that Access Bank undertakes CSR interventions in education, healthcare, environmental sustainability, and economic empowerment; however, awareness of these efforts among residents remains low. Moreover, opinions regarding the relevance of the initiatives were mixed, with some respondents acknowledging their benefits while others perceived them as misaligned with community priorities. The study concludes that although Access Bank’s CSR initiatives hold potential for fostering community development, their limited visibility and insufficient stakeholder engagement weaken overall impact. It recommends enhanced publicity strategies and stronger community participation in the planning and implementation of CSR programmes to ensure greater alignment with local development needs.